Effect of Horizontal Resolution of Printer on Trueness of 3D-Printed Provisional Crown: An In Vitro Study - Hai, Pham Nhu; Son, Tong Minh; Anh, Nguyen Viet; Ngoc, Vo Truong Nhu; Tra, Nguyen Thu (European Journal of General Dentistry, 2023)
Objectives Provisional crowns play an integral role in prosthodontic therapy and need to be fabricated with high accuracy to ensure good marginal fit and proper contour. The aim of this study is to evaluate the effect of 3D printer's horizontal pixel resolution on trueness of the intaglio surface, external surface, and marginal area and the actual marginal adaptation of the interim crowns.Materials and Methods A gypsum reference model of mandible with a prepared right first molar was scanned with a dental laboratory scanner (AutoScan-DS-MIX, Shining 3D) and a digital provisional crown was design using the computer-aided design (CAD) software (Exocad). The provisional crown was manufactured by two printers with different horizontal resolutions (Sonic Mini 4K Printer and Sonic Mini 8K Printer). The printed crowns were scanned using the aforementioned scanner. The trueness of the external surface, internal surface, and marginal area of the provisional crowns was evaluated by comparing the scanned data with the reference CAD design data using a 3D inspection software (Geomagic Control X, 3D systems). The trueness of the crown manufactured by two printers was compared by a two-sided test (α = 0.05). Finally, the marginal adaptation of the provisional crowns was evaluated on the printed removable dies and compared.Results The results revealed that there was a significant difference in the trueness of the marginal area and the marginal adaptation (p < 0.05).Conclusions It can be concluded that the trueness of provisional crown marginal area and the marginal adaptation was affected by the horizontal resolution of the 3D printer.
Keywords: provisional crown; horizontal resolution; trueness; 3D printer; interim crown; marginal area